Teologi Pendidikan: Menafsirkan Warisan Klasik untuk Menjawab Tantangan Global - Amiruddin Amiruddin; M. Anzaikhan (Raudhatun Najah Publisher, 2023)
Ideally, Islamic education should develop dynamically in response to contemporary changes while maintaining its theological foundations derived from the Qur'an, the Sunnah, and the intellectual legacy of classical Muslim scholars. However, the current reality reveals persistent dichotomies between religious and secular knowledge, weak integration of theological values into educational practices, and limited reinterpretation of the classical heritage in addressing global challenges such as globalization, the digital revolution, artificial intelligence (AI), and moral crises. This study aims to examine the genealogy of the theology of education in Islam, analyze its transformation within contemporary educational contexts, and formulate a theological paradigm capable of responding to global challenges. This research employs a qualitative library research approach using content analysis of primary and secondary sources. The findings indicate that reinterpreting the values of tawḥīd, khilāfah, amānah, 'ilm, adab, and maqāṣid al-sharī'ah provides an integrative, adaptive, and contextual paradigm for Islamic education. This paradigm integrates spiritual, intellectual, moral, social, and technological dimensions, enabling Islamic education to preserve its theological identity while effectively contributing to sustainable global civilization.